Diarrhea Incidence in Tanah Bumbu, South Kalimantan, Under A Spatial Approach - Hasan, Annida; Ferdina, Ayunina Rizky; Sembiring, Wulan Sari Rasna Giri (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Indonesia has seen an increase in diarrhea incidence from 4.5% in 2013 to 6.8% in 2018. South Kalimantan, diarrhea is still a common disease with a relatively high incidence rate. In Tanah Bumbu itself, the incidence of diarrhea from 2014 to 2019 was among the top 10 most common diseases. The percentage of patients served in 2019 was 33.26% of the detection targets. While in infants, only 3.4% of the number of detection targets. This study aims to see the spatial description and influence of the districts’ condition in Tanah Bumbu Regency with the diarrhea incidence. This research took place in the ten districts of Tanah Bumbu Regency. The analysis used in this study was SAR to see the relationship between districts and the incidence of diarrhea and other factors. The results showed that in Tanah Bumbu, factors that affected the incidence of diarrhea include population density (p-value 0.0001), access to quality drinking water (p-value 0.0001), and health facilities (p-value 0.0001).